Imaging retinal progenitor lineages in developing zebrafish embryos - Jusuf, Patricia R.; Harris, William A.; Poggi, Lucia (Cold Spring Harbor protocols, 2013)
In this protocol, we describe how to make and analyze four dimensional (4D) movies of retinal lineage in the zebrafish embryo in vivo. 4D consists of three spatial dimensions (3D) reconstructed from stacks of confocal planes plus one time dimension. Our imaging is performed on transgenic cells that express fluorescent proteins under the control of cell-specific promoters or on cells that transiently express such reporters in specific retinal cell progenitors. An important aspect of lineage tracing is the ability to follow individual cells as they undergo multiple cell divisions, final migration, and differentiation. This may mean many hours of 4D imaging, requiring that cells be kept healthy and maintained under conditions suitable for normal development. The longest movies we have made are ∼50 h. By analyzing these movies, we can see when a specific cell was born and who its sister was, allowing us to reconstruct its retinal lineages in vivo.